2002
DOI: 10.1046/j.1365-2389.2002.00429.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of soil strength on root growth: experiments and analysis using a critical‐state model

Abstract: Summary Roots grow thicker in compacted soil, even though it requires greater force for a large object to penetrate soil than it does for a small one. We examined the advantage of thickening in terms of the stresses around a root penetrating with constant shape, rather than the stresses around an expanding cylinder or sphere, as has been studied previously. We combined experiments and simulations of the stresses around roots growing in compacted soils. We measured the diameter of pea roots growing in sandy loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
90
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 20 publications
5
90
0
3
Order By: Relevance
“…The missing root fraction in the MRI data is relatively well defined, and thus poses no problem for data interpretation. Root diameters have been found to depend on soil strength (Kirby and Bengough, 2002), soil water content (Kuchenbuch et al, 2006), or nutrition levels (Zobel et al, 2007), and thus the ability to accurately determine diameters may be of importance for many studies. It is difficult to say what the precise accuracy is of our diameter estimates, as we do not have a coregistration of the magnetic resonance images with the WinRHIZO scans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The missing root fraction in the MRI data is relatively well defined, and thus poses no problem for data interpretation. Root diameters have been found to depend on soil strength (Kirby and Bengough, 2002), soil water content (Kuchenbuch et al, 2006), or nutrition levels (Zobel et al, 2007), and thus the ability to accurately determine diameters may be of importance for many studies. It is difficult to say what the precise accuracy is of our diameter estimates, as we do not have a coregistration of the magnetic resonance images with the WinRHIZO scans.…”
Section: Discussionmentioning
confidence: 99%
“…The soil strength was 40 kPa at full water holding capacity, increasing to 500 kPa when dried as measured using a penetrometer (Eijkelkamp, Giesbeek, The Netherlands). This is sufficiently low for good root growth (Kirby and Bengough, 2002) even at the relatively high bulk densities.…”
Section: Soil Substratementioning
confidence: 97%
“…Root growth into granular materials resembles the propagation of an open-mode axisymmetric discontinuity, so one may wonder whether plants use similar strategies to optimally invade soils. Data show that the rate of elongation and the rate of radial expansion are related to mechanical conditions at the tip of the root: difficult invasion conditions promote radial expansion of the root before the root tip advances further into the 'weakened' soil mass ahead of the tip (Hettiaratchi et al, 1990;Kirby & Bengough, 2002;Gregory, 2006 A particle-level analysis and a macroscale effective stress numerical simulation follow.…”
Section: Introductionmentioning
confidence: 99%
“…This adjustment of roots to increased soil strength reduces the risk of root buckling and decreases the mechanical stress acting on the root during penetration (Materechera et al, 1992;Kirby and Bengough, 2002;Chimungu et al, 2015). Root thickening in response to increased soil strength has been observed in a wide range of species under field and laboratory conditions and often coincides with increased cortical area (Atwell, 1990a;Materechera et al, 1992;Grzesiak et al, 2013;Siczek et al, 2013;Chen et al, 2014;Hernandez-Ramirez et al, 2014;Colombi and Walter, 2016).…”
mentioning
confidence: 99%
“…Root thickening in response to increased soil strength has been observed in a wide range of species under field and laboratory conditions and often coincides with increased cortical area (Atwell, 1990a;Materechera et al, 1992;Grzesiak et al, 2013;Siczek et al, 2013;Chen et al, 2014;Hernandez-Ramirez et al, 2014;Colombi and Walter, 2016). Since root thickening decreases penetration stress and stabilizes roots, thick roots are likely to be an advantage in soils with increased mechanical impedance (Materechera et al, 1992;Kirby and Bengough, 2002;Chimungu et al, 2015). A recent study showed that the genotypic cortical thickness in maize is related to bending strength and, hence, to the risk of root buckling (Chimungu et al, 2015).…”
mentioning
confidence: 99%